1996
DOI: 10.1177/073953299601700110
|View full text |Cite
|
Sign up to set email alerts
|

How Gender and Ethnicity Affected Primary Coverage

Abstract: Media coverage of a white, male candidate was the most issue-oriented, but coverage of a female candidate was the most favorable in the 1994 Illinois Democratic gubernatorial primary election.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This argument has already been made in the United States, with a call for journalists to portray women as they would the men (Powers et al, 1996). Henderson (1999, p. 159) quotes one female MP as saying that it is trendy to have women and families in politics, but argues that no male MP is asked how they will look after their children, as they have wives.…”
Section: Resultsmentioning
confidence: 99%
“…This argument has already been made in the United States, with a call for journalists to portray women as they would the men (Powers et al, 1996). Henderson (1999, p. 159) quotes one female MP as saying that it is trendy to have women and families in politics, but argues that no male MP is asked how they will look after their children, as they have wives.…”
Section: Resultsmentioning
confidence: 99%
“…Female candidates' agendas receive less coverage than those of men (Falk, 2008;Kahn, 1996;Powers et al, 1996). However, gendered differences do not stop there.…”
Section: Story Contentmentioning
confidence: 99%
“…However, gendered differences do not stop there. Other studies have found that, when covering women candidates, media outlets tend to focus on 'feminine' themes (Aday & Devitt, 2001;Kahn, 1992Kahn, , 1996Kahn & Goldenberg, 1991;Powers et al, 1996). When the media employ simplified versions of stereotypes -such as women being best suited to deal with social problems-they convey a message to voters (Entman, 1993;Goffman, 1974).…”
Section: Story Contentmentioning
confidence: 99%